Development of interactive learning multimedia based on Somatic, Auditory, Visual, Intellectual (SAVI) approach assisted by Articulate Storyline 3 on circular motion material - Adela Zulfa Sabila; Nana Nana; Ifa Rifatul Mahmudah (Universitas Ahmad Dahlan, 2024)
There are limited learning approaches and laboratory facilities regarding developing interactive learning multimedia for circular motion material. Therefore, this research aims to develop interactive multimedia learning based on the Somatic, Auditory, Visual, and Intellectual (SAVI) approach assisted by Articulate Storyline 3 on circular motion material. This research is a type of research and development of the ADDIE model. The respondents involved were 31 students in class XI MIPA B and XI MIPA C. Experts validated the product from media, material, and language aspects. Product validity was analyzed using the Aiken V technique. The Aiken V index scores were 0.89, 0.92, and 0.89 for assessing media, material, and language aspects. The practicality assessment resulted in an average of 96%, which shows high practicality in the learning context. In conclusion, this SAVI-based interactive multimedia has been validated by experts and is well received by students. So, it has proven to be very suitable for effective learning at Darussalam Rajapolah Integrated High School, Tasikmalaya. This research implies that the development of interactive learning multimedia based on the Somatic, Auditory, Visual, and Intellectual (SAVI) approach assisted by Articulate Storyline 3 on circular motion material can be a solution to overcome the limitations of traditional learning approaches and laboratory facilities in teaching the concept of circular motion.